Intrahousehold preferences for humanitarian assistance—Who prefers what: Evidence from internally displaced households in Sudan - Abushama, Hala; Nigus, Halefom Yigzaw; Abay, Kibrom A.; Siddig, Khalid (International Food Policy Research Institute, 2025)
Understanding the preferences of beneficiaries for what form of humanitarian aid they receive is critical for improving the effectiveness of such aid in conflict-affected settings that are characterized by rapidly changing markets and information asymmetries. This paper examines intrahousehold differences in preferences for in-kind, cash, and hybrid assistance among internally displaced households in Sudan, with particular attention to gender, decision-making power, and agency differences. While cash remains the most preferred modality, about half of the respondents reported favoring in-kind or hybrid assistance options. On average, women report a 7-percentage point higher preference for in-kind transfers than men, but with some variation across states. Preferences are strongly shaped by intrahousehold decision-making—spouses, particularly women, who control decisions over the use of aid are more likely to prefer cash, while those with less agency in such decisions favor in-kind assistance. We also find suggestive evidence that limited market access and self-control constraints are associated with a higher preference for in-kind transfers. These findings highlight the importance of agency and intrahousehold dynamics in shaping aid modality preferences and offer practical insights for designing more equitable humanitarian and social protection interventions in contexts with significant population displacement.